Three Turano-European species of the Temnothorax interruptus group (Hymeno ptera: Formicidae) demonstrated by quantitative morphology - Csősz, Sándor; Salata, Sebastian; Borowiec, Lech (Myrmecological News, 2018)
Keywords: Morphometrics; species delimitation; exploratory analyses; gap statistic; biogeography; new species

Light at the end of the tunnel: Integrative taxonomy delimits cryptic species in the Tetramorium caespitum complex (Hymenoptera: Formicidae) - Wagner, Herbert C.; Arthofer, W.; Seifert, B.; Muster, C.; Steiner, F. M.; Schlick-Steiner, B. C. (Myrmecological News, 2017)

Two new species of the "ultimate" parasitic ant genus Teleutomyrmex KUTTER, 1950 (Hymenoptera: Formicidae) from the Western Palaearctic - Kiran, Kadri; Karaman, Celal; Lapeva-Gjonova, Albena; Aksoy, Volkan (Myrmecological News, 2017)
Two new "ultimate" parasitic ant species, Teleutomyrmex seiferti KIRAN & KARAMAN sp.n. and Teleutomyrmex buschingeri LAPEVA-GJONOVA sp.n., are described from one site each in Turkey and Bulgaria. The hosts belong to Tetra- morium cf. chefketi FOREL, 1911. The findings increase the number of described Teleutomyrmex species to four.
Keywords: Taxonomy; ants; Formicidae; Teleutomyrmex; social parasites; new species; Turkey; Bulgaria

Changes in the zoogeographical structure of ants (Hymenoptera: Formicidae) caused by urban pressure in the Sofia region (Bulgaria) - Antonova, Vera; Penev, Lyubomir (Myrmecological News, 2006)
A comparison of the zoogeographical peculiarities of the myrmecofauna in urban and non-urban habitats in Sofia region is performed. The proportion of the widespread Holarctic species was twice as high in the urban as compared to the non-urban sites. Also Euro-Caucasian elements are well represented in the urban sites. The share of South-Transpalaearctic, Eurasian steppe and Boreo-Montane elements is low or such elements are absent from the urban sites.
Keywords: ants; Bulgaria; Formicidae; urban landscape; zoogeography

First record of the slave-maker ant Harpagoxenus sublaevis (Nylander, 1849) from Bulgaria (Hymenoptera: Formicidae) - Antonova, Vera (Myrmecological News, 2009)
Harpagoxenus sublaevis (Nylander, 1849) was found among ants taken in pitfall traps set in the Alibotoush Reserve, Slavjanka Mountain in southwestern Bulgaria. This species is new to the Bulgarian myrmecofauna that recently numbered about 130 species.
Keywords: Bulgaria; Formicidae; Harpagoxenus sublaevis; social parasite

First records of three ant species (Hymenoptera: Formicidae) from Bulgaria - Lapeva-Gjonova, Albena (Myrmecological News, 2011)
Three Mediterranean ant species – Camponotus aegaeus EMERY, 1915, Camponotus gestroi EMERY, 1878 and Crematogaster auberti EMERY, 1869 – were found on Bulgarian territory for the first time. The report of Camponotus aegaeus for Bulgaria is the first for continental Europe as well. The total number of known ant species for Bulgaria increases to more than 160.
Keywords: ants; Bulgaria; Camponotus; Crematogaster; Formicidae